Aplikasi Event Organizer Wedding X berbasis Android - andre halim soenarko; Kristo Radion Purba; Alexander Setiawan (Jurnal Infra, 2017)
Wedding Planner service is not uncommon thing in this modern era, the complexity and a various requirements which are needed to prepare a wedding ceremony could bring hassle for each couple, especially with the expenses and many other factors. Sometimes all of the required needs which may vary is a troublesome to prepare for each couple, whether it be the schedule, finding and meeting the vendors and preparing other required needs for the wedding ceremony.With an application that is installed on a gadget with Android operation system, this service is more convenient to access and easy to use. In addition to save time and money, client could find the required vendors such as decoration, cake and wedding dress. Client can also be reminded by the event organizer part about the required needs for the wedding ceremony. The event organizer could also provide direct notifications for the client when the process agreement with the vendor is met. This application is an information system based on mobile device which is designed with HTML5 and using Phonegap’s software.The results of this implementation could gengerate an application for the client in order to find the required vendors, exchanging messages with the event organizer part as well as submitting events that will help in completing the needs of weeding ceremony. Meanwhile the event organizer part can assist the clients regarding the to-do-list for the required needs of the ceremony. The event organizer part can also exchange messages with the vendor if there are transaction progress. The event organizer can also upload files which are required by the client. The vendor part can edit profiles and interact with the event organizer. From the questionnaire result can conclude this application answers the needs 79%